Criminal minds. The tenth season [videorecording (DVD)] - Davis, Jeff, 1975- (Paramount Pictures : CBS DVD, 2015)
To solve the most twisted crimes, the FBI's Behavioral Analysis Unit (BAU) explores the darkest places--inside the depths of Criminal Minds. Seasoned undercover, FBI Agent Kate Callahan joins the elite team led by Supervisory Special Agent Aaron Hotchner as they pursue a serial killer who hacks his victims beyond all recognition. Experienced profiler David Rossi is dogged by mysterious woman from his past, while Dr. Spencer Reid grapples with the death of a mentor.